2004
DOI: 10.3748/wjg.v10.i11.1643
|View full text |Cite
|
Sign up to set email alerts
|

Tumor type M2pyruvate kinase expression in gastric cancer, colorectal cancer and controls

Abstract: Tumor M(2)-PK has a higher sensitivity than markers CEA and CA72-4, and is a valuable tumor marker for the detection of gastrointestinal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 12 publications
2
35
0
Order By: Relevance
“…The serum level of tumor M2-PK among normal people should be low compared to that among colorectal lesion patients and should not vary by gender and age. The average level of serum M2-PK among 158 normal people was 2.96 U/mL which is much lower than those in clinical patients or volunteers [22,23] . Our community-based results for serum levels of M2-PK associated with the TNM Classification of Malignant Tumors and Duke's staging in CRC are supported by these patient-based clinical studies [22,23] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The serum level of tumor M2-PK among normal people should be low compared to that among colorectal lesion patients and should not vary by gender and age. The average level of serum M2-PK among 158 normal people was 2.96 U/mL which is much lower than those in clinical patients or volunteers [22,23] . Our community-based results for serum levels of M2-PK associated with the TNM Classification of Malignant Tumors and Duke's staging in CRC are supported by these patient-based clinical studies [22,23] .…”
Section: Discussionmentioning
confidence: 99%
“…The average level of serum M2-PK among 158 normal people was 2.96 U/mL which is much lower than those in clinical patients or volunteers [22,23] . Our community-based results for serum levels of M2-PK associated with the TNM Classification of Malignant Tumors and Duke's staging in CRC are supported by these patient-based clinical studies [22,23] . Because our result for normal serum level of M2-PK was based on a large sample size (158) from communities in a CRC mass screening program, it is reliable and can be generalizable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, serum ENO2 is considered to be a prognostic factor in small cell lung, breast, and prostrate cancer (36)(37)(38)(39). Finally, PKM2 seems to be a more sensitive marker than conventional tumor markers such as CEA and CA72-4 for the post-operative surveillance of gastrointestinal cancer (40)(41)(42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, two independent studies revealed that the use of M2-pyruvate kinase for the detection of CRC has a sensitivity of 48-58% and a specificity of 90-95%. Furthermore, when combined with CEA, the sensitivity of M2-pyruvate increases without decreasing the specificity (58,59).…”
Section: M2-pyruvate Kinasementioning
confidence: 99%